Comportamento do esmalte de dentes decíduos após desafio desmineralizante em função de materiais restauradores: estudo ao microscópio de luz polarizada - Ramos, Carolina Júdica [UNESP] (2003)
The aim of this in vitro study was to evaluate by polarized light microscopy the development of artificial carious lesions in primary teeth adjacent to different restorative materials. Buccal class V restorations were prepared in 40 deciduous human molars with margins in enamel which were ramdonly divided into four groups (n=10): a poliacid modified resin composite (Dyract AP); a hybrid resin composite (Z-250); a resin-modified glass ionomer cement (Vitremer) and a conventional glass ionomer cement (Fuji IX GP Fast). After the restorative procedures, all teeth surfaces were coated with nail polish, except for the restoration area and 1 mm rim of tooth structure. ln order to induce artificial carious lesions, the specimens were immersed into an acidified gel (pH 4,5) for 14 days at room temperature. After this, the specimens were prepared for polarized light microscopy in an imbibition's media of water. The results showed the development of caries lesions in all groups. The data was analysed by Kruskal-Wallis and Dunn's test (5%) and the specimens restored with glass ionomer cement exhibited- the depth of caries significantly lower than the group restored with composite resin. lt was concluded that the restorative material can influence the demineralization of primary enamel